You were always mine : [large type] a novel - Pride, Christine; Piazza, Jo (Thorndike Press large print top shelf., 2023)
"Cinnamon Haynes has fought hard for a life she never thought was possible--a good man by her side, a steady job, and a cozy house in a quaint town. Daisy Jacobs's hopes for her future are threatened when she gets unexpectedly pregnant. She hides this development and then makes a drastic decision with devastating consequences. When Cinnamon finds an abandoned baby in a park and takes the newborn into her home, the ripple effects risk exposing Cinnamon's own past. These two women must unite for the sake of the baby they both love in their own unique way when Daisy's grandparents, who would rather die than see one of their own raised by a Black woman, threaten to take custody."--Back cover.